Clarification of the authorship, type species, and date of the genus Taxigramma (Diptera: Sarcophagidae) - Evenhuis, Neal L.; Pape, Thomas (Zootaxa, 2014)
The authorship and date of publication of the genus Taxigramma is found to be established by Macquart in 1850, with the type species Miltogramma heteroneura Meigen, 1830, by monotypy. A history of the name and its junior synonym Heteropterina Macquart, 1854, is given.